Rill erosion on an unpaved loess road surface: Effects and control. (28th December 2022) - Kou, Pinglang; Xu, Qiang; Jin, Zhao; Tao, Yuxiang; Yunus, Ali P.; Xia, Ying; Zhang, Shuo; Pu, Chuanhao
Abstract: Rill erosion on unpaved roads is widespread and highly destructive on the Loess Plateau of China, but the exploration of its evolution mechanism is scarce. In this study, a multiphase runoff scour experiment was performed on an abandoned field road in the Loess Plateau, China. Using a terrestrial laser scanner (TLS), scour experiments are used to evaluate the dynamic evolution of rill erosion and fill. The results show that soil erosion decreases significantly after the initial surge. During the first scouring, the depths of erosion and fill reached their maximum, which were 5.49 ± 7.62 mm and 5.72 ± 16.37 mm, respectively, and the fourth erosion and fill rates are only 24% and 35% of the first. Unlike the upstream and midstream, which are dominated by erosion, the downstream is mainly characterized by fill, and the downstream fill depth is 1.46 times the erosion depth; however, this ratio is 0.52 and 0.74 in the upstream and midstream, respectively. A comparison of the erosion raster with slope change revealed that rapid slope change due to erosion was mainly concentrated at 10–15°. In addition, a comparison of the fill raster with the slope found that slopes greater than 30° during the second scouring tended to flatten out most by filling, as the hydrodynamic forces of steep slopes were easily dissipated. The relationship between slope, erosion, and fill is complex and variable for each scouring. Orthophotos revealed that the U‐shaped bottom topography was conducive to concentrated overland flow, which significantly worsens the rill erosion on the road surface. This indicates that even if the slope is very gentle, the terrain easy to collect water will cause considerable erosion damage. Prevention of rill erosion on the unpaved loess road surface, therefore, requires focused drainage development. This study provides important further scientific insights into the evolution of loess road rill erosion and road erosion damage to inform erosion hazard management in the context of fragile loess landscapes.